How to read Barthes' Image-Music-Text - White, Ed, 1945- (How to read theory., 2012)
Roland Barthes remains one of the most influential cultural theorists of the postwar period and Image-Music-Text collects his most influential essays. Ed White provides students with a clear guide to this essential but difficult text. As students are increasingly expected to write across a range of media, Barthes work can be understood as an early mapping of what we now call interdisciplinary or multidisciplinary study. The books detailed section-by-section readings makes Barthes most importantwritings accessible to undergraduate readers. This book is a perfect companion for teaching and learning Barthes ideas in cultural studies and literary theory.